The Effect of Differentiated Learning on Understanding of Concepts In The Form of Practicum on The Opportunity Material In Grade X - Tertius Gowasa; Simon M. Panjaitan; Sanggam P. Gultom (STABN RADEN WIJAYA WONOGIRI, 2020)
This study was conducted to identify the extent to which differentiated learning influences students’ understanding of mathematical concepts. The focus of this study was the probability material, which was taught to grade X students at SMA Negeri 1 Percut Sei Tuan in the 2025/2026 Academic Year. The experimental class was taught with a differentiated learning approach in the form of practicums. Data collection instruments consisted of observations and tests. Based on the results of the analysis, a significance value (Sing. 2-tailed) of <0.001 was obtained, which is below the 5% significance level (0.05). this indicates that there is a significant influence of differentiated learningin the form of practicums on students’ understanding of mathematical concepts on the probability material in the grade X of SMA Negeri 1 Percut Sei Tuan. The results of the data analysis showed that the influence of differentiated learningin in the from of practicums on conceptual understanding was 71,3%.